DFT Study on Effect of Hydrogen-Bond Formation on the Adsorption of Ethanol on Pd(111) Surface - Huang, Bin; Chen, Rong; Shui Chen, Quan (Asian Journal of Chemistry, 2012)
DFT calculations have been performed to explore the ethanol adsorption on Pd (111) surfaces. Relative energies, equilibrium geometries, vibrational frequencies and electronic structures of monomer, dimer and one-dimensional (1D) chain of ethanol molecules adsorbed at the surface were investigated and analyzed. The calculations indicate that ethanol molecules prefer to adsorb at a top sites of the Pd (111) surface and the adsorption is exothermic. Adsorbed ethanol molecules are likely to form dimer and chain through the hydrogen bond interactions. The results also show that there are red shifts of n(O-H) frequencies for ethanol molecules adsorbed over the Pd (111) surface.